Development of an ultrastructure preservation protocol for platelet and fibrin networks utilizing high pressure freezing and subsequent comparison of new and established protocols - Pretorius, Etheresia (University of Pretoria, 2014)
Dissertation (MSc)--University of Pretoria, 2013.